Opposite roles of serotonin and neuropeptide FMRFamide in the regulation of epigenetic processes involved in the longterm memory formation - L. N. Grinkevich; O. V. Vorobiova (Вавиловский журнал генетики и селекции)
Epigenetic modifications are studied intensively to understand mechanisms of long-term memory. We have shown that histone H3 methylation is important for the defense reflexes formation in the mollusk Helix lucorum. We suggested that these epigenetic modifications are controlled by facilitatory and inhibitory pathways involved in the long-term memory formation. Serotonin and neuropeptide FMRFamide play opposite roles in the formation of defensive reflexes. Serotonin strengthens synaptic connections between neurons of the network, and FMRFamid is an inhibitory transmitter leading to long-term depression. To study the epigenetic regulation of the processes involved in the long-term memory formation, we performed comparative studies on the serotonin and FMRFamide effects on histone H3 methylation in the CNS of the Helix. We found that the incubation of the CNS with serotonin induces methylation of histone H3 at both activating (Н3K4me3) and inhibitory (Н3K9me2) sites, while incubation with FMRFamide has an opposite effect reducing methylation of histone H3 in the subesophageal complex of ganglia, important for defensive behaviour. We observed a different methylation pattern of histone H3 in the cerebral ganglia involved in signal processing of food stimuli, where serotonin did not affect the methylation of histone H3 at the activator site and reduced methylation at the inhibitory site, while FMRFamid had no effect on methylation. The data indicate that the facilitatory and inhibitory processes mediated by serotonin and FMRFamide can interact at the epigenetic level, through histone H3 methylation by activating or inhibiting it, respectively. This may underlie the convergence of the activator and inhibitory pathways involved in the long-term memory formation and underlie following regulation of the expression of genes involved in long-term plasticity.